Analisis Kerusakan pada Rotor Pompa Sentrifugal G-1-12-C di PT X - Melkias, Alvera Apridalianti; Indriyani Indriyani; Fachry Fadian (SURYA TEKNIKA, 2024)
Damage to a tool can cause the production process to stop and cause downtime. Preventing damage to equipment is by managing the maintenance process. This process includes preventive maintenance, corrective maintenance and predictions of damage (predictive maintenance) which is carried out periodically. Centrifugal pumps have the working principle of converting kinetic energy (speed) of liquid into potential (dynamic) energy through an impeller that rotates in the casing. This pump is an impeller that is mounted on a shaft with bearings at both ends. Damage to the pump rotor has a serious impact on the performance and reliability of the pump system. The rotor is one of the main components responsible for transferring mechanical energy into the pumped fluid, so damage to the rotor can affect pump efficiency, operational life, and damage to pump components. Analysis of damage to the pump rotor was carried out by testing using the NDT method. NDT testing includes Visual Inspection, Magnetic Particle Inspection, Liquid Penetrant and Balancing Rotor. Based on the results of the tests and analysis carried out, it was found that there was damage to several parts of the pump rotor, such as corrosion on the pump shaft, dirt on the surface, and scratches on the mechanical seal seat area with a depth of approximately 0.50 mm. Rotor unbalance or the center of gravity of the shaft rotation is not the same as the geometric center of the shaft. The impeller was found to be in poor condition, high metal of radial impeller and medium to heavy rubbing at wearing impeller. The DE and NDE distance sleeves are not in a bad condition and there are scratches.